Earthquake Decay Analysis to Determine the Afters Thock end Time in West Sumatra in 2021-2023 Using The Omori-Utsu Method - Dhea Fitria; Syafriani Syafriani; Hamdi Hamdi; Letmi Dwiridal (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2025)
West Sumatra, situated at the convergence of the Indo-Australian and Eurasian tectonic plates, experiences frequent earthquakes and aftershocks due to the complex geological setting. This study utilizes the Omori-Utsu method, a modified version of Omori’s law by seismologist Tokiji Utsu, to estimate aftershock duration. Data on aftershocks from significant earthquakes (magnitude ≥5.5M) between 2021 and 2023 were accessed through the BMKG earthquake catalog. The study finds that aftershock durations vary significantly depending on the earthquake's tectonic origin. The longest recorded aftershock duration occurred after the West Pasaman earthquake on February 22, 2022, lasting 21 days, while the shortest was one day following the Mentawai earthquake on September 11, 2022. These variations highlight the influence of tectonic structures on aftershock activity, with subduction zones exhibiting shorter decay times. This research provides critical insights into earthquake behavior, aiding in disaster preparedness and mitigation strategies for the West Sumatra region.